👤

Rezolvați ecuația: (x + 1)² - 5x² = 2(x - 3)²-(x + 2)².

Răspuns :

Răspuns:

Pentru a rezolva ecuația, putem începe prin a simplifica fiecare parte a ecuației.

(x + 1)² - 5x² = 2(x - 3)² - (x + 2)²

(x² + 2x + 1) - 5x² = 2(x² - 6x + 9) - (x² + 4x + 4)

x² + 2x + 1 - 5x² = 2x² - 12x + 18 - x² - 4x - 4

-4x² - x² + 2x² + 2x + 4x + 12x - 1 - 18 + 4 = 0

-3x² + 18x - 15 = 0 | ×(-1)

3x² - 18x + 15 = 0

a= 3. ∆=b²-4ac

b=-18. ∆=324-4×3×15=> ∆=√144=> ∆=12

c=15

x1,2= -b±√∆ / 2a => x1= 18+√144 / 2×3 = 30/6= 5

x2= 18-√144/ 2×3= 6/6= 1